2020
DOI: 10.1007/s11906-020-01089-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Metabolic Syndrome in Persons with HIV

Abstract: Purpose of Review With the advent of highly active antiretroviral therapy (ART), the life span of persons with HIV (PWH) has been nearly normalized. With aging, prevalence of the metabolic syndrome (MetS), including hypertension, has increased in the HIV population and exceeds that in the general population in some studies. This is due to a combination of traditional risk factors in addition to the effects attributable to the virus and ART. We review recent findings on the mechanisms contributing to MetS and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 57 publications
5
43
0
2
Order By: Relevance
“…Importantly, it should be noted that blood lipids and body weight in PHIV also depend on the baseline characteristics of the study participants, despite some concerns about modern antiretrovirals [12,17,47–50], and that the adherence to educational and therapeutic interventions could be important in the prevention of cardiovascular risk, besides the choice of ART. Finally, we found a higher risk of MS in older study participants, as expected [51] and in those with higher CD4 counts, which was unexpected. Low CD4 nadir has been reported as a risk factor for MS and hypertension [51,52], while current high CD4 count is not usually considered as a risk factor.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Importantly, it should be noted that blood lipids and body weight in PHIV also depend on the baseline characteristics of the study participants, despite some concerns about modern antiretrovirals [12,17,47–50], and that the adherence to educational and therapeutic interventions could be important in the prevention of cardiovascular risk, besides the choice of ART. Finally, we found a higher risk of MS in older study participants, as expected [51] and in those with higher CD4 counts, which was unexpected. Low CD4 nadir has been reported as a risk factor for MS and hypertension [51,52], while current high CD4 count is not usually considered as a risk factor.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, we found a higher risk of MS in older study participants, as expected [51] and in those with higher CD4 counts, which was unexpected. Low CD4 nadir has been reported as a risk factor for MS and hypertension [51,52], while current high CD4 count is not usually considered as a risk factor. However, it is possible that higher CD4 counts could reflect, in general, good health and well‐being, but also that study participants with higher CD4 count were those with better adherence to ART, and thus were free from toxicities like nausea or gastrointestinal side effects.…”
Section: Discussionsupporting
confidence: 85%
“…Our data showed that the frequency of comorbid conditions was higher among HIV-positive individuals > 40 years compared to those ≤40 years of age ( Abou Hassan et al submitted manuscript ). In accordance with previous reports from our group ( Hammad et al accepted manuscript JIDC ) and worldwide [ 14 , 49 52 ], the most commonly reported comorbidities among our study participants were hypertension and hyperlipidemia followed by CVD and diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, blocking or preventing RAS activation in AT can reduce oxidative stress, improve insulin resistance and reduce inflammation (173,174). Interactions between the RAS and HIV infection have been described, and could contribute to AT inflammation, but also to the onset of metabolic syndrome and hypertension in PLWH (175,176).…”
Section: Oxidative Stress Endothelial Dysfunction and The Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%